Weed management in coriander (Coriandrum sativum L.) at varying levels of nitrogen - Sharma, S S Yadav, I Choudhary, L R Yadav, O P (Journal of Spices and Aromatic Crops, 2016)
A field experiment was conducted to study the effect of weed control treatments and nitrogen (N) levels on weed dynamics, weed control efficiency, nutrient depletion by weeds, yield of coriander and weed competition index. All the weed control treatments significantly reduced the density and dry weight of weeds and nutrient depletion as compared to weedy check. Oxadiargyl at 0.06 kg ha-1 + hand weeding (HW) at 40 days after sowing (DAS) represented the lowest weed density and controlled the weeds to the extent of 94.9%. Two hand weedings done at 20 and 40 DAS and pendimethalin at 1.0 kg ha-1 + HW at 40 DAS were found to be the most superior treatments in reducing density, intensity and dry weight of weeds and increasing weed control efficiency. These treatments controlled the weeds to the extent of 95.1% and 95.4%, respectively at harvest stage than weedy check and showed lower weed infestation of 17.4 and 18.1%, respectively. The lowest nutrient depletion due to weeds was obtained with pendimethalin at 1.0 kg ha-1 + HW at 40 DAS treatment which saved 54.80 kg N, 8.31 kg P and 49.22 kg K ha-1, respectively than weedy check. Two HWs at 20 and 40 DAS and oxadiargyl at 0.06 kg ha-1 + HW at 40 DAS also reduced the nutrient depletion to the extent of 94.8 and 94.5% of N; 95.0 and 94.7% of P and 94.9 and 94.6% of K, respectively in comparison to weedy check. Two hand weeding treatment gave the highest seed yield (1.37 t ha-1) among all the treatments and was closely followed by pendimethalin at 1.0 kg ha-1 + HW at 40 DAS which also increased the seed yield by a margin of 0.84 t ha-1 over weedy check, and registered the lowest weed competition index of 0.7%.